Analisis Pengaruh Sistem Pengendalian Internal, Ketaatan Aturan Akuntansi, dan Kompetensi Sumber Daya Manusia Terhadap Penurunan Accounting Fraud Pada Unit Pengelola Kegiatan (UPK) di Kabupaten Sragen - Ardika Yuda Pamungkas; Heppy Purbasari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Accounting fraud is a form of deviation from standard operating practices in an agency related to financial reporting. Internal control systems, compliance with accounting rules, and human resource competencies play a role in reducing accounting fraud. This study aims to analyze the effect of internal control systems, compliance with accounting rules, and human resource competencies on reducing accounting fraud in Activity Management Units (UPK) in Sragen Regency. The population in this study were UPK administrators in Sragen Regency. The sample determination used purposive sampling. The respondents of the study were 48 UPK administrators consisting of the chairman, secretary, Verification Team (TV), Supervisory Board (BP) and treasurer in UPK in each sub-district in Sragen Regency. The data obtained were then processed using multiple regression analysis. The results of this study include: first, the internal control system variable does not have a significant effect on the variable of reducing accounting fraud in UPK in Sragen Regency. Second, the variable of compliance with accounting rules does not have a significant effect on reducing accounting fraud in UPK in Sragen Regency. Third, the variable of human resource competency has a significant effect on reducing accounting fraud in UPK in Sragen Regency. This study can be utilized by the Central Government and Regional Governments to formulate policies related to reducing accounting fraud in UPK throughout Indonesia or specifically in UPK in Sragen Regency.